2000
DOI: 10.1063/1.883020
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals and Carbon Materials

Abstract: Carbon atoms can be found in a variety of structures, including the tetrahedra of diamond, the stacked planes of graphite, and the celebrated fullerene spheres and nanotubes. The graphite family alone includes a rich variety of materials, ranging from pencil “lead” to interstellar dust to chimney soot, and from metallurgical coke to activated charcoal for water filtration to lightweight composites for aerospace components—such as the nose cone of the space shuttle, for which carbon composites were chosen becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 9 publications
3
51
0
Order By: Relevance
“…Thus, during stabilization, the gradual increase in T g by cross-linking reactions leads to the formation of rigid oxidized segments (Braun et al, 2005) that, although are necessary to avoid fiber swelling and fusion and may increase the carbon yields, could be detrimental to structural carbon order (Hurt and Chen, 2000). However, it has been recently reported that the interconnection in fused CFs enhances the mechanical properties of both the thermostabilized and carbonized materials (Dallmeyer et al, 2014a).…”
Section: Lignin-based Carbon Fibers For Structural Applicationsmentioning
confidence: 99%
“…Thus, during stabilization, the gradual increase in T g by cross-linking reactions leads to the formation of rigid oxidized segments (Braun et al, 2005) that, although are necessary to avoid fiber swelling and fusion and may increase the carbon yields, could be detrimental to structural carbon order (Hurt and Chen, 2000). However, it has been recently reported that the interconnection in fused CFs enhances the mechanical properties of both the thermostabilized and carbonized materials (Dallmeyer et al, 2014a).…”
Section: Lignin-based Carbon Fibers For Structural Applicationsmentioning
confidence: 99%
“…Coating optical substrates with concentrated lyotropic solutions in a manner that flow-aligns the rods is known to produce, upon drying, dichroic organic layers upon drying 17 . Dried films of indanthrone disulfonate have a density of 1.69 g/cm 3 by picnometry 17 and XRD analysis reveals crystallinity with a d-spacing of 0.336 nm in the _-stacks and molecular order parameters from 0.86-0.91 17 . For the present work indanthrone disulfonate was acquired as an ammonium salt solution from the firm Optiva (South San Francisco), which uses the solutions for fabrication of thin film organic polarizers 17 .…”
mentioning
confidence: 99%
“…3 is the uniform perpendicular alignment, which establishes the unique crystal orientation that characterizes this nanomaterial. Heat treatment of these phases can coalesce the layers and produce longer and straighter fringes, but does not alter the basic crystal symmetry established in the young, lowtemperature carbon material 3 . Figure 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations